Digestive enzymes activities in Oreochromis niloticus fed diet supplemented with recombinant growth hormone - Apriana Vinasyiam; Muhammad Agus Suprayudi; , Alimuddin (Jurnal Akuakultur Indonesia)
ABSTRACT